Optimal scheduling of microgrids based on multi-objective improved grey wolf optimization algorithm - Hu, Bowei; Xu, Minghu; Ji, Jianwei (2024 4th International Conference on Electronics, Circuits and Information Engineering (ECIE), 2024)
The development of an optimal scheduling strategy is crucial for microgrid systems, which can ensure the cost-effectiveness of the system. For this reason, this paper proposes a microgrid optimal scheduling strategy based on the multi-objective improved grey wolf algorithm, to further improve the comprehensive benefits of microgrid optimal scheduling. First, on the traditional microgrid model containing multiple distributed power sources, a comprehensive optimal scheduling model is constructed by considering the environmental benefits and combining the demand-side load profile and time-sharing tariff. Then, the objective function for maximizing the comprehensive benefits is designed and solved by using the multi-objective grey wolf algorithm based on multi-objective co-optimization for optimal scheduling. Finally, the effectiveness of the method proposed in this paper is verified by simulation analysis and comparison of actual examples.